A meta-analysis and systematic review of the prevalence of mitochondrially encoded 12S RNA in the general population: Is there a role for screening neonates requiring aminoglycosides? - Titus S Ibekwe (African Journal of Paediatric Surgery, 2015)
Background: This was a meta-analysis and systematic review to determine the global prevalence of the mitochondrially encoded 12S RNA (MT-RNR1) genetic mutation in order to assess the need for neonatal screening prior to aminoglycoside therapy. Materials and Methods: A comprehensive search of MEDLINE, EMBASE, Ovid, Database of Abstracts of Reviews of Effect, Cochrane Library, Clinical Evidence and Cochrane Central Register of Trials was performed including cross-referencing independently by 2 assessors. Selections were restricted to human studies in English. Meta-analysis was done with MetaXL 2013. Results: Forty-five papers out of 295 met the criteria. Pooled prevalence in the general population for MT-RNR1 gene mutations (A1555G, C1494T, A7445G) was 2% (1-4%) at 99%. Conclusion: Routine screening for MT-RNR1 mutations in the general population prior to treatment with aminoglycosides appear desirable but poorly supported by the weak level of evidence available in the literature. Routine screening in high-risk (Chinese and Spanish) populations appear justified.